2005
DOI: 10.1128/ec.4.10.1725-1735.2005
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Bound Bas1 Recruits Pho2 To Activate ADE Genes in Saccharomyces cerevisiae

Abstract: Expression of the genes in the ADE regulon of Saccharomyces cerevisiae is repressed by the presence of purine bases in the extracellular medium and derepressed when cells are grown in the absence of purines. Derepression requires the transcriptional activators Bas1 and Pho2, as well as the biosynthetic intermediates 5-phosphoribosyl-4-succinocarboxamide-5-aminoimidazole (SAICAR) and 5-phosphoribosyl-4-carboxamide-5-aminoimidazole (AICAR). In this study, we investigated if nuclear localization and binding to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 44 publications
5
26
0
Order By: Relevance
“…Further analyses using Bas1 and Pho2 fused to the transcription activation domain of VP16 suggested that Bas1 binds to the ADE gene promoters and recruits Pho2 (Pinson et al 2000). This was further demonstrated by chromatin immunoprecipitation (ChIP) analysis (Som et al 2005).…”
Section: Regulation Of Pyrimidine Metabolismmentioning
confidence: 98%
“…Further analyses using Bas1 and Pho2 fused to the transcription activation domain of VP16 suggested that Bas1 binds to the ADE gene promoters and recruits Pho2 (Pinson et al 2000). This was further demonstrated by chromatin immunoprecipitation (ChIP) analysis (Som et al 2005).…”
Section: Regulation Of Pyrimidine Metabolismmentioning
confidence: 98%
“…Previous studies have shown that Bas1 is constantly present at ADE promoters in an inactivated state. Upon induction, Bas1 undergoes a conformation change and recruits Pho2 (41). Interestingly, previous works also show that Pho2 directly interacts with NuA4 in vitro and in vivo, a step considered crucial to preset the promoter of the PHO5 gene for induction (26).…”
Section: Loss Of Eaf1 Affects Genome-wide Htz1 Enrichmentmentioning
confidence: 99%
“…In an adenine-sufficient environment, the transcription of ADE genes is basal/repressed. The deprivation of available adenine will trigger the expression of a series of ADE genes in order to adapt to the environment (39)(40)(41). The fact that YPD media are poor in adenine allowed us to detect the implication of NuA4 in the regulation of ADE gene expression in the microarray experiment.…”
Section: Loss Of Eaf1 Affects Genome-wide Htz1 Enrichmentmentioning
confidence: 99%
“…Bas1p is required for the activation of adenylate biosynthetic genes under conditions of adenine depletion and in an SAGA-and SWI/SNF-dependent manner (18,33). In addition, Bas1p activates not only adenylate biosynthesis but also the one-carbon metabolic regulon under glycine-replete conditions (39).…”
mentioning
confidence: 99%
“…Purine biosynthesis, one of the major metabolic pathways influenced by one-carbon metabolism, is executed by many ADE genes (4). It has been known that the expression of the one-carbon regulon and ADE genes were regulated mostly in a cooperative manner at the transcriptional level (18,24,33). Gcn4p and Bas1p are well-known transcription factors mediating this regulation (26,39).…”
mentioning
confidence: 99%